2022
DOI: 10.22373/sjhk.v6i1.9954
|View full text |Cite
|
Sign up to set email alerts
|

Merantau in The Ethnic Tradition of Minangkabau: Local Custom Without Sharia Basis?

Abstract: Customary practice in Minangkabau is based on sharia, and sharia is based on the Qur’an (as provisioned in the proverb Adat Bersandi Syarak, Syarak Bersandi Kitabullah-ABS/SBK). As a customary practice, is merantau in the Minangkabau tradition based on sharia? This article explains the relationship between custom and sharia in Minangkabau’s merantautradition. This study is a qualitative research with in-depth interview data collection techniques and literature study. In-depth interviews were conducted with fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Research by Zainuddin et al 33 and Assaad et al 34 shows the encounter and collaboration of local culture and Islamic law which vividly shows how those two can be either in harmony or in conflict. On the other hand, Beccmann's research found ulema fighting customary traditions that contradict Islamic law 35 which strengthens that this case repeatedly happens in diverse contexts. When Minangkabau ulema used the method of war to solve the contradictions, ulema around the Samin community provided continuous understanding in a peaceful manner.…”
Section: Data Compiled From Researchmentioning
confidence: 84%
“…Research by Zainuddin et al 33 and Assaad et al 34 shows the encounter and collaboration of local culture and Islamic law which vividly shows how those two can be either in harmony or in conflict. On the other hand, Beccmann's research found ulema fighting customary traditions that contradict Islamic law 35 which strengthens that this case repeatedly happens in diverse contexts. When Minangkabau ulema used the method of war to solve the contradictions, ulema around the Samin community provided continuous understanding in a peaceful manner.…”
Section: Data Compiled From Researchmentioning
confidence: 84%
“…Referring to Ash-Shiddiqy in Siregar et al (2022), all laws apply due to habit. Therefore, habits appear to become community agreements and comply with form the customary law Harmonization of customary and Islamic law in the gama tradition... (Rosdalina Bukido, et.al) (Howell, 2018).…”
Section: The Relationship Between Customary and Islamic Law In The Ga...mentioning
confidence: 99%
“…This happens because they need each other and contribute to each other. The human relationship with art cannot be avoided without realizing it, in everyday life, people's activities are always closely related to art [2]. Likewise, traditional art is the result of community art that depicts local culture and identity passed down from the older generation to the younger generation.…”
Section: Introductionmentioning
confidence: 99%